Selected novel aspects in pathogenesis of lupus erythematosus – interdisciplinary view - Kalińska-Bienias, Agnieszka; Foroncewicz, Bartosz; Bienias, Piotr; Kowalewski, Cezary (Dermatology Review/Przegląd Dermatologiczny, 2016)
Lupus erythematosus is an autoimmune disease characterized by complex immune disturbances concerning humoral and cell-mediated immune responses. Despite intensive research, many pathological processes regarding this disorder remain unexplained. During interdisciplinary investigations on the etiology of lupus and its complications special interest has recently been referred to heat-shock proteins, antibodies directed against such proteins and galectin-3. These issues are extensively studied not only by dermatologists and rheumatologists, but also by cardiologists (in terms of cardiovascular complications) and nephrologists (in terms of lupus nephritis). This study presents the current state of dermatological, nephrological and cardiological knowledge on this topic.